Draft Special Component Plan 1988-89 Government of Pondicherry - Planning Commission (Planning Commission, 1988)
The Union Territory of Pondicherry consists of four regions , namely , Pondicherry , Karaikal, Mahe and Yanam lying geographically isolated from one another Pondicherry region which is on the past coast about 160 Kms. south of Madras is the largest of these and consists of 12 scattered areas interspearsed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is surrounded by Thanjavur District of Tamil Nadu. Yanam region is located about 650 Kms. north of Madras near Kakinada in Andhra Pradesh. Mahe region is on the west coast near Tellicherry in Kerala.
Union Territory of Pondicherry